Efficacy of Embolization in Acquired Uterine Vascular Malformations: An Experience in Tertiary Care Centre in India - Inampudi, Vineel; Nimmalapudi, Sunanda (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective: To determine the efficacy of Uterine Artery Embolization in patients with bleeding acquired uterine arteriovenous malformations (AVMs).Methods: A prospective review of all patients who underwent Uterine Artery Embolization at our institution between July 2015 and April 2022 was performed. 225 patients were diagnosed with a uterine vascular malformation on doppler and corresponding MRI imaging. All patients underwent transcatheter embolization of the uterine arteries. Embolic agents in the 375 procedures included Histoacryl glue only (n = 326), polyvinyl alcohol (PVA) particles and Histoacryl glue (n = 29), PVA particles (n = 5), Gelfoam (n = 5), coils (n = 4), PVA particles and coils (n = 3), Histoacryl glue and Gelfoam (n = 2), and Histoacryl glue and coils (n = 1).Results: A total of 375 embolization procedures were performed in 225 patients. 90 patients required repeat embolization for recurrence of bleeding. The technical success rate of embolization was 100%. The clinical success rate was 92%: bleeding was controlled in 222 of 225 patients and three patients underwent a hysterectomy. 60 of the 225 patients had uneventful intrauterine pregnancies carried to term. The 210 patients who underwent successful embolization had no recurrence of bleeding at a median follow-up of 53 months (range, 5-122 months) after treatment. 15 patients were eventually lost to follow-up. One minor complication (0.4%) of non-flow-limiting dissection of the internal iliac artery occurred.Conclusion: Uterine Artery Embolization is a safe, effective, minimally invasive method to treat uterine AVMs with long-term efficacy, which can provide the preservation of fertility.
Keywords: Uterine arteriovenous malformations; Uterine artery embolization; Uterus; Endovascular; Histoacryl glue